THE EFFECT OF TRAINING AND INFORMATION TECHNOLOGY AND ADDITIONAL EMPLOYEE INCOME ALLOWANCES ON EMPLOYEE PERFORMANCE IN THE REGIONAL SECRETARIAT AGENCY OF EAST KUTAI REGENCY - Florida, Maria; Ruliana, Titin; Yudhyani, Eka (STKIP Pesisir Selatan, 2025)
Employee performance at the East Kutai Regency Regional Secretariat needs to be improved through various influencing factors. Factors such as training, information technology, and employee supplementary income allowances (TPP) are believed to play a crucial role in motivating and improving employee performance. Positive performance will encourage employees to perform better, while a lack of support can lead to decreased motivation and work discipline.This study used a quantitative method with a descriptive approach and a population of 114 employees, with a sample of 89 employees drawn using a random sampling technique. Data collection was conducted through a questionnaire, and data analysis used SmartPLS to test the effect of independent variables on employee performance.The purpose of this study was to determine the direct and indirect effects of training, information technology, and supplementary income benefits on employee performance through information technology as an intervening variable. The results showed that training had a positive but insignificant effect on employee performance. Meanwhile, information technology and supplementary income benefits had a positive and significant effect on performance. Furthermore, training and supplementary income benefits also had an indirect effect through the use of information technology. Simultaneously, these three variables contributed significantly to improving employee performance within the agency.